Quality- a Factor of Management in Road Transport of Goods - Jakomin, Livij; Smerdu, Ivan (Promet - Traffic&Transportation, 2012)
Providing services on a quality level is an important factorof management in the trade rivalry for the control over the market.The factors affecting quality comprise technical factors andoperational and organisational ones. The technical factors includethe choice, the due care and maintenance of the vehicle.The operational and organisational factors are the quality offer,performing the transport service, the response in case of action,and the information efficiency.The necessity to control the total quality management is theresponsibility of the management. All staff members must participatein the improvement of quality management in their particularworking environment. Improved quality managementprovides for a higher safety of business operation and jobs, resultingin enhanced social security, which is gaining importancein mutual relations.